CBA (4-chloro-2-(2-chlorophenoxy)acetamido) benzoic acid) inhibits TMEM206 mediated currents and TMEM206 does not contribute to acid-induced cell death in colorectal cancer cells - Kappel, Sven; Melek, Korollus; Ross-Kaschitza, Daniela; Hauert, Barbara; Gerber, Christian E.; Lochner, Martin; Peinelt, Christine (Frontiers in Pharmacology, 2024)
Introduction: Upon activation at low pH, TMEM206 conducts Cl− ions across plasma and vesicular membranes. In a (patho)physiological context, TMEM206 was reported to contribute to acid-induced cell death in neurons, kidney and cervical epithelial cells. We investigated the role of TMEM206 in acid-induced cell death in colorectal cancer cells. In addition, we studied CBA as a new small molecule inhibitor for TMEM206. Methods: The role of TMEM206 in acid-induced cell death was studied with CRISPR/Cas9-mediated knockout and FACS analysis. The pharmacology of TMEM206 was determined with the patch clamp technique. Results: In colorectal cancer cells, TMEM206 is not a critical mediator of acid-induced cell death. CBA is a small molecule inhibitor of TMEM206 (IC50 = 9.55 µM) at low pH, at pH 6.0 inhibition is limited. Conclusion: CBA demonstrates effective and specific inhibition of TMEM206; however, its inhibitory efficacy is limited at pH 6.0. Despite this limitation, CBA is a potent inhibitor for functional studies at pH 4.5 and may be a promising scaffold for the development of future TMEM206 inhibitors.